Japanese clinical practice guidelines for allied disorders of Hirschsprung's disease, 2017. Issue 5 (May 2018) - Muto, Mitsuru; Matsufuji, Hiroshi; Taguchi, Tomoaki; Tomomasa, Takeshi; Nio, Masaki; Tamai, Hiroshi; Tamura, Masanori; Sago, Haruhiko; Toki, Akira; Nosaka, Shunsuke; Kuroda, Tatsuo; Yoshida, Masahiro; et al.
Abstract: Background: Despite the presence of ganglion cells in the rectum, some patients have symptoms similar to those of Hirschsprung's disease. A consensus has yet to be established regarding the terminology for these diseases. We defined this group of diseases as "allied disorders of Hirschsprung's disease" and compiled these guidelines to facilitate accurate clinician diagnosis and provide appropriate treatment strategies for each disease. Methods: These guidelines were developed using the methodologies in the Medical Information Network Distribution System (MINDS). Of seven allied disorders, isolated hypoganglionosis; megacystis‐microcolon‐intestinal hypoperistalsis syndrome; and chronic idiopathic intestinal pseudo‐obstruction were selected as targets of clinical questions (CQ). In a comprehensive search of the Japanese‐ and English‐language articles in PubMed and Ichu‐Shi Web, 836 pieces of evidence related to the CQ were extracted from 288 articles; these pieces of evidence were summarized in an evidence table. Results: We herein outline the newly established Japanese clinical practice guidelines for allied disorders of Hirschsprung's disease. Given that the target diseases are rare and intractable, most evidence was drawn from case reports and case series. In the CQ, the diagnosis, medication, nutritional support, surgical therapy, and prognosis for each disease are given. We emphasize the importance of full‐thickness intestinal biopsy specimens for the histopathological evaluation of enteric ganglia. Considering the practicality of the guidelines, the recommendations for each CQ were created with protracted discussions among specialists. Conclusions: Clinical practice recommendations for allied disorders of Hirschprung's disease are given for each CQ, along with an assessment of the current evidence. We hope that the information will be helpful in daily practice and future studies.